The Impact of Online Political Participation on Offline Political Engagement: Examining the Moderating Role of Age - Nishat Ansar; Dr. Shazia Hashmat (Indus Journal of Social Sciences, 2025)
This study investigated the impact of online political participation on offline political engagement the role of age. A structured questionnaire and purposive sampling method were used to collect data from two universities i.e., Bahria University, Islamabad, and Foundation University School of Science & Technology Islamabad. The sample size was 386. The unit of analysis consisted of students from different departments of these universities. The quantitative research method was applied in this research. Survey analysis was used for quantitative research, and the questionnaire was furnished among students. Firstly, the normality of missing values was determined, followed by examining the reliability and validity of the survey questionnaire in SPSS and AMOS, respectively. Data were analyzed using techniques like linear regression through SPSS. All the results were significant and in line with the proposed model. It was found that online explained significant variation in offline. Age moderated the relationship between the online & offline political participation. Age effectively moderates the relationship between independent and dependent variables.